The need for an objective measure in septorhinoplasty surgery: are we any closer to finding an answer?. (December 2015) - Andrews, P.J.; Choudhury, N.; Takhar, A.; Poirrier, A.L.; Jacques, T.; Randhawa, P.S.
Abstract : Objectives: To assess the reliability of nasal inspiratory peak flow (NIPF) in providing a clinically accurate objective measure following functional septorhinoplasty by comparing it to the validated disease‐specific quality‐of‐life questionnaire, SNOT‐22. Studies so far have demonstrated poor correlation between bilateral NIPF and symptom‐specific nasal questionnaires following septorhinoplasty. Design: To perform a prospective comparative analysis between NIPF and the validated disease‐specific quality‐of‐life questionnaire SNOT‐22 and to determine whether a correlation exists following septorhinoplasty surgery. Setting: The Royal National Throat Nose and Ear Hospital, London. Participants: A total of 122 patients (78 males, 44 females; mean age 33.5 ± 12.2 years) were recruited from the senior authors rhinology clinic and underwent functional septorhinoplasty surgery. Main outcome measures: Preoperative and postoperative nasal inspiratory peak flow (NIPF) measurements were performed in addition to the completion of three subjective quality‐of‐life and symptom assessment tool questionnaires; Sinonasal Outcome Test 22 (SNOT‐22), Nasal Obstruction Symptom Evaluation (NOSE) and Visual Analogue Scale (VAS: 0–10). Results: The mean preoperative NIPF was 88.2 L/min, and the postoperative value was 101.6 L/min and showed a significant improvement following surgery ( P  = 0.0064). The mean total SNOT‐22 score improved significantly from 48.6 to 26.6 ( P  < 0.0001); the NOSE score from 14.1 to 6.6 ( P  < 0.0001); and the Visual Analogue Scale (VAS) blockage score from 6.9 to 3.2 ( P  < 0.0001). All individual domains assessed showed improvements postoperatively, but no correlation was found between the NIPF and SNOT‐22 score. Equally, we did not find a correlation between NIPF and the symptom‐specific NOSE questionnaire and the nasal blockage domain on the Visual Analogue Scale (VAS) scale. Conclusion: We have demonstrated that NIPF does not correlate with the SNOT‐22 disease‐specific questionnaire, although both outcomes significantly improve postoperatively. At present, we are still lacking a clinically accurate objective measure of nasal function for the evaluation of patients undergoing septorhinoplasty surgery.